Multiple sclerosis in Finland 2018—Data from the national register. (29th July 2019) - Laakso, Sini M.; Viitala, Matias; Kuusisto, Hanna; Sarasoja, Taneli; Hartikainen, Päivi; Atula, Sari; Tienari, Pentti J.; Soilu‐Hänninen, Merja
Abstract : Objectives: Finland is a high‐risk multiple sclerosis (MS) region, but a national MS register has not existed until 2014. In this paper, we present the Finnish MS register variables and data collected by 31 December 2018. Materials and Methods: Numbers and data counts of MS patients in the register (ICD‐10 code G35) are presented. The disease types and proportion of patients receiving disease‐modifying treatments (DMTs) were analysed in five hospital districts with most complete data sets. MS prevalence in Finland was estimated using administrative hospital discharge data as an additional resource. Results: There were a total of 8722 MS patients in the Finnish MS register by 31 December 2018 (71.5% females). Mean age at MS diagnosis was 38.7 years and peak prevalence was at age 50‐54 years. Disease course was relapsing remitting (RRMS) in 66.7%, secondary progressive (SPMS) in 13.5%, and primary progressive (PPMS) in 7.9% of the 5365 MS patients in the selected districts with most complete data. A total of 66.0% of RRMS patients, 19.6% of SPMS patients and 9.9% of PPMS patients were receiving DMTs. By combining MS register data with databases of those hospitals that had not joined the register, the nationwide prevalence estimate was between 10 and 11 thousand patients (corresponding to crude prevalence 180‐200/100 000). Conclusions: The Finnish MS register is currently used in 15/21 Finnish hospital districts. By register integration into the electronic patient files, the coverage of the register has increased to approximately 80% of the estimated Finnish MS population.